Implementation of Character Education Values in Social Studies Learning of Elementary School - Siska, Yulia; Yufiarti; JAPARIDZE, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The researcher conducts empirical study of the implementation of the value of character education in learning Social Studies at Elementary School in Bandarlampung. The virtue in this research lies in in-depth discussion of the value of character education in textbook. In addition, the teacher's perceptions of the relation to the implementation of the value of character education are also discussed in Social Studies material for the fifth grade of Elementary School in Bandarlampung. This research uses a qualitative descriptive design with content analysis techniques. Researcher describes systematically, factual, and accurate information on the facts and and the causal relationship of the phenomenon which is examined. To understand the meaning of objects or social phenomena. Based on the results and discussion, stated:1) The process of implementing the value of elementary character education in Bandarlampung consists of the stages of planning, implementation, and evaluation; 2) Integrated thematic textbook for fifth grade Elementary School students has very high eligibility. Based on the average suitability score of the integrated textbook for Elementary Schoolstudents in Bandarlampung, is in very good category, which is 0.81, with a Relative Frequency of 81%; 3) Compatibility of integrated thematic books with character education includes 11 (eleven) character values, namely: religious, tolerance, discipline, creative, democratic, curiosity, national spirit, respect for achievement, friendliness, love to read, and care for the environment.